(untitled) (CIPEEX, 2024)
THE IMPLEMENTATION OF A CASH FLOW MAKES IT POSSIBLE TO AGGREGATE THE RESPONSIBILITIES OF ACCOUNTS PAYABLE AND FINANCIAL OBLIGATIONS THAT COMPANIES ASSUME AND WHICH ARE GENERALLY CARRIED OUT THROUGH THE CREDIT MODULE. THESE ARE TRANSACTIONS IN WHICH PURCHASES OF GOODS OR RAW MATERIALS OCCUR, AND ARE ALSO INTENDED FOR COSTS AND EXPENSES INVOLVED IN THE OPERATION OF THE COMPANY. THEREFORE, THE QUESTION WAS CHOSEN AS PROBLEMATIC: WHAT ARE THE IMPACTS OF IMPLEMENTING CASH FLOW IN AN INDUSTRY IN THE STRUCTURING AND IMPLEMENTATION PHASE DUE TO A SPLIT? THE GENERAL OBJECTIVE WAS TO UNDERSTAND WHAT A CASH FLOW IS AND WHAT IT IS FOR AND WHAT ITS STRUCTURAL COMPONENTS ARE. THUS, THE METHODOLOGY APPLIED WAS THE CASE STUDY CARRIED OUT AT THE COMPANY SOL INDUSTRIA E COMERCIO DE COLCHOES E ESTOFADOS LTDA, WHICH WENT THROUGH THE SPLIT PROCESS AND STARTED A NEW CNPJ IN 2021. DATA COLLECTION WAS CARRIED OUT THROUGH DOCUMENT ANALYSIS, WHOSE DOCUMENTS FOR ANALYSIS WERE PROVIDED BY THE ADMINISTRATIVE SUPERVISOR OF THE COMPANY STUDIED, AND THE COMPANY’S BALANCE SHEET AND INCOME STATEMENT FOR THE END OF THE YEAR 2021 WERE COLLECTED TO ESTABLISH THE COMPANY’S CONDITION IN THIS PERIOD AND HOW THE APPLICATION OF A CASH FLOW IS INTERESTING FOR ITS STRUCTURING. IT WAS POSSIBLE TO REALIZE, BASED ON THE PREDICTED AND REALIZED CASH FLOW, THAT OBTAINING DATA FOR THE COMPANY IS ESSENTIAL TO DETERMINE THE BEST FINANCIAL PATH, WITH THE CASH FLOW, IT WILL BE POSSIBLE TO ESTABLISH ALL EXPENSES AND REVENUES, INVENTORY CONTROL AND CREATION OF LONG-TERM STRATEGIES THAT HELP THE COMPANY ESCAPE THE LOSS IT FINDS ITSELF IN DUE TO THE SPLIT, THUS GENERATING A POSITIVE IMPACT FOR THE COMPANY STUDIED. &NBSP; KEYWORDS:&NBSP; INDUSTRY. COMPANY. CASH FLOW.